HBR's 10 must reads on innovation. (HBR's 10 must reads (Series), 2013)
Innovation luminaries including Peter Drucker, Rosabeth Moss Kanter, and Clayton Christensen provide insights and advice that you need to: - Adapt innovations from the developing world to wealthier markets - Plan all-new ventures by testing and tweaking - Manage risk across an innovation portfolio - Avoid classic pitfalls such as stifling innovation with rigid processes - Iterate to arrive at the best possible product offering.